Three-dimensional laplace adomian decomposition method and singular pseudoparabolic equations - Eltayeb, Hassan; Elgezouli, Diaa Eldin; Kilicman, Adem; Bachar, Imed (Hindawi, 2021)
In this work, the solution of the linear, nonlinear, and coupled system fractional singular two-dimensional pseudoparabolic equation is examined by using a three-dimensional Laplace Adomian decomposition method (3-DLADM). Analysis of the method is discussed, and some demonstrative examples are mentioned to confirm the power and accuracy of the recommended method, and numerical analysis is applied to sketch the exact and approximate solution.